Psychoemotional state of patients 60+ years old with chronic cerebrovascular insufficiency relocating with their family from the far north - Klimatckaia, Liudmila G.; Zaitseva, Olga I. (Family Medicine & Primary Care Review, 2016)
Background. In the Soviet period, people came to work in the Far North of the Krasnoyarsk Territory. Now they are retired. Remaining retired in the North is not economically feasible. Resettlement of unemployed elderly people to the more favorable southern climatic zones of central Siberia is connected with a demographic situation. For families 60+ years old, the “From the Extreme North to the South” program was created. The article presents the results of studies on the psychoemotional state of migrants 60+ years old. Objectives . To study the psychoemotional state of patients 60+ years old with chronic cerebrovascular insufficiency when adapting from the North to the South. Material and methods. 98 migrants from the North to the South were examined. These were people with a chronic insufficiency of brain blood circulation at the age of 60+ years old. Patients were tested utilizing the G. Eysenck and A.S. Zigmond, R.P. Snaith. Hospital Anxiety and Depression Scale. Results . Various types of personality were revealed: extroverts – 60.2% (59 people), introverts – 39.8% (39 people). Emotionally stable migrants 60+ years old – 25.5% (28 people). Emotionally unstable – 74.5% (70 people). The sociability combination with impulsiveness was characteristic with a high level of emotional instability (17.27 ± 0.26 points). At very high level (19.5 ± 0.31 points), low self-esteem and an emotional block were revealed. Conclusions . 1. Emotionally stable migrants 60+ years old readapt fairly. 2. High and very high levels of neuroticism demonstrate the formation of anxiety disorders and restriction of adaptive opportunities in migrants 60+ years old. Treatment and prophylactic actions are provided to them.